EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE TIME TOKEN DAN SNOWBALL THROWING TERHADAP PRESTASI BELAJAR MATEMATIKA DITINJAU DARI SIKAP SISWA - ERNY UNTARI (LP3M Universitas Muhammadiyah Muara Bungo, 2021)
The purposes of this study are to determine: (1) which one has a better achievement, students who are taught by learning the model Time Token or Snowball Throwing type. (2) which one has a better achievement, students who have a high, middle, or low achievement attitude. (3) Is there any interaction between learning model and achievement attitude towards achievement. This study is a quasi experimental research with 2x3 factorial design. The population of this study is all students VII Grade SMPN 1 Kasreman in the academic year 2018/2019. Sampling was done by random technique. The total of samples is 60 students. The instruments used to collect data are the test of prior knowledge in mathematics, achievement attitude questionnaire and mathematics achievement test. The testing of hypothesis uses two-way analysis of variance with unequal cell.The testing of hypothesis concludes that (1) Students who taught by learning model of Snowball Throwing type have better achievement than students who taught by learning model of Time Token type.(2) Students who have high achievement attitude have better achievement than students who have low achievement attitude, also students who have middle achievement attitude have same achievement than students who have low achievement attitude.(3) There isn’t interaction between learning model and achievement attitude towards achievement.